2019
DOI: 10.1039/c9ob02273b
|View full text |Cite
|
Sign up to set email alerts
|

Esterase-sensitive trithiane-based hydrogen sulfide donors

Abstract: 1,3,5-Trithiane functionalized with esterase-sensitive ester groups on the methylene linkers was developed as a class of enzymatic hydrolysis-based hydrogen sulfide (H2S) donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…ContinuedPluth et al are consistent well with the known fact that low concentration of H 2 S stimulates cellular bioenergetics in both aerobic and anaerobic metabolism by acting as an inorganic electron donor, while high level of H 2 S compromises the mitochondrial ETC via inhibition of cytochrome c oxidase 83. Park et al described two 1,3,5-trithiane-based H 2 S donors (donors 50 and 51, Figure7E), which were equipped with one or two ester linkages 260. Studies showed that donors 50 and 51 released H 2 S in a controllable manner under the catalysis of esterase.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…ContinuedPluth et al are consistent well with the known fact that low concentration of H 2 S stimulates cellular bioenergetics in both aerobic and anaerobic metabolism by acting as an inorganic electron donor, while high level of H 2 S compromises the mitochondrial ETC via inhibition of cytochrome c oxidase 83. Park et al described two 1,3,5-trithiane-based H 2 S donors (donors 50 and 51, Figure7E), which were equipped with one or two ester linkages 260. Studies showed that donors 50 and 51 released H 2 S in a controllable manner under the catalysis of esterase.…”
supporting
confidence: 76%
“…Park et al described two 1,3,5‐trithiane‐based H 2 S donors (donors 50 and 51 , Figure 7E), which were equipped with one or two ester linkages 260 . Studies showed that donors 50 and 51 released H 2 S in a controllable manner under the catalysis of esterase.…”
Section: H2s Donors and H2s‐releasing Hybrid Moleculesmentioning
confidence: 99%
“…Esterase enzymes are omnipresent in human cells and, as their name implies, catalyze the hydrolysis of esters [ 121 ]. Not surprisingly, H 2 S liberation from a donor that is initiated by esterase-catalyzed hydrolysis is a common approach [ 122 , 123 , 124 , 125 , 126 , 127 ]. In general, the molecular framework is designed in such a way that upon ester hydrolysis, the resultant alcohol undergoes a self-immolative step that results in the eventual release of H 2 S. Donor P2 ( Figure 14 ) illustrates this approach, as an unstable hydroxymethyl persulfide is unveiled after esterase-catalyzed hydrolysis [ 128 ].…”
Section: H 2 S Donors That Protect Against Myocard...mentioning
confidence: 99%
“…Similarly, the turn-on fluorogenic probes for other antioxidant enzymes such as GR and GPx were also developed recently for estimating their cellular expression levels. 31,32 Regarding the release of H 2 S from organic compounds, only a few studies with an enzyme–responsive donation of H 2 S (non-fluorogenic donors) involving esterase 14,33 and bacterial nitroreductase 34 are reported. However, real-time monitoring of the H 2 S release from those non-fluorogenic donors was not feasible due to the lack of a proper monitoring process.…”
Section: Introductionmentioning
confidence: 99%